Canadian Muslim Excellence: A Time to Celebrate, Educate, and Reflect - Amtul, Zareen; King, April; Lia, Adita (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2024)
This study redresses the limited presence of stories of Muslims in Canadian archival history and curriculum, drawing attention to the racial issues as an antidote, so that public awareness of anti-Islamophobia strategy can be made known. The authors searched, preserved, and distributed the diverse and inclusive stories of Muslim Canadians by employing a comprehensive, multidisciplinary strategy to map the political, ideological, institutional, and economic contributions of Canadian Muslims who are working for a better Canada. The authors made these stories readily available and accessible as an open educational resource under a Creative Commons’ license, by creating and constructing a digital archive. This research also works towards developing resources and connections for a range of audiences to develop learning aids to teach Muslim Canadians history. The fabric of this country would not be the same, if it were not for diversity. Muslim Canadians are valued contributors to the Canadian climate, and deserve to be celebrated, rather than mistreated. Sharing the stories of Muslim Canadians who have had a positive impact on this country is intended to increase the positive messaging surrounding some of the wonderful contributions Muslim Canadians have accomplished.